2016
DOI: 10.18632/oncotarget.11168
|View full text |Cite
|
Sign up to set email alerts
|

The tri-peptide GHK-Cu complex ameliorates lipopolysaccharide-induced acute lung injury in mice

Abstract: The tripeptide-copper complex glycyl-l-histidyl-l-lysine-Cu (II) (GHK-Cu) is involved in wound healing and tissue remodeling. Although GHK-Cu exhibits anti-aging and tissue renewing properties, its roles in acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) are still unknown. Therefore, we examined the effects of GHK-Cu in lipopolysaccharide (LPS)-induced RAW 264.7 macrophages in vitro and ALI in mice in vivo. GHK-Cu treatment reduced reactive oxygen species (ROS) production, increased superoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…And are widely used as an inflammation model to evaluate the potential protection of a drug in vitro . The excessive production of pro‐inflammatory cytokines increases the immune response, which in turn results in inflammatory cascade and tissue injury .Thus, inhibiting the release of inflammatory cytokines may be a target for anti‐inflammatory drug therapies. Therefore, in this study, we used macrophages instead of primary endometrial epithelial cells to explore the underlying mechanism of PD, which could have more general applicability—that is, PD may also play a similar role in other inflammatory diseases that have been confirmed in our previous studies .…”
Section: Discussionmentioning
confidence: 99%
“…And are widely used as an inflammation model to evaluate the potential protection of a drug in vitro . The excessive production of pro‐inflammatory cytokines increases the immune response, which in turn results in inflammatory cascade and tissue injury .Thus, inhibiting the release of inflammatory cytokines may be a target for anti‐inflammatory drug therapies. Therefore, in this study, we used macrophages instead of primary endometrial epithelial cells to explore the underlying mechanism of PD, which could have more general applicability—that is, PD may also play a similar role in other inflammatory diseases that have been confirmed in our previous studies .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with GHK, its copper (II)-chelated form shows a more prominent antioxidant and anti-inflammatory effect in both in vitro and in vivo studies. Pretreatment of RAW 264.7 macrophage cells with GHK-Cu has been shown to significantly decrease ROS levels induced by lipopolysaccharide (LPS), increase levels of SOD activities and total GSH, and decrease levels of TNF-α and IL-6 production through the suppression of NF-κB p65 and p38 MAPK signaling [22]. Both signaling pathways are key regulators of inflammation and pro-inflammatory responses, which are considered targets for developing anti-inflammatory therapeutic agents [23][24][25][26].…”
Section: The Anti-inflammatory Effect Of Ghkmentioning
confidence: 99%
“…Both signaling pathways are key regulators of inflammation and pro-inflammatory responses, which are considered targets for developing anti-inflammatory therapeutic agents [23][24][25][26]. In the LPS-induced acute BRIEF lung injury mouse model, treatment of GHK-Cu also significantly suppressed TNF-α and IL-6 expression with a significant decrease of both NF-κB p65 and p38 MAPK signaling, suggesting that GHK-Cu is useful for the development of novel anti-inflammatory therapies [22]. We have also found that pretreatment of GHK-Cu has a robust antioxidant effect in WI-38 cells treated with 150uM of hydrogen peroxide, decreasing the ROS level to almost 60 percent (Figure 1).…”
Section: The Anti-inflammatory Effect Of Ghkmentioning
confidence: 99%
“…The authors propose that GHK-Cu prevents activation of NFkB's p65 and p38 MAPK. P38 protein kinases have pro-inflammatory activity, and p65 activation plays an important role in cancer development [37].…”
Section: Anti-oxidant Actions Of Ghk-cumentioning
confidence: 99%